As in the topic, my question is to prove $$\sum_{i=1}^{n}\frac{x_{i}^3}{x_{i+1}^2}\geq \sum_{i=1}^{n}\frac{x_{i}^2}{x_{i+1}}$$We know that $x_{n+1}=x_{1}$ and $x_{1},x_{2}, x_{3},..., x_{n}\in \mathbb{R}_{+}$.
As I suspect that it would be to cool if all $x_{i}$ were equal, and question is marked as tough one, after a few hours my brain stopped without producing anything reasonable so I ask you for hints how to move it. Everything will be appreciated. Thanks in advance.


Hint:We can derive your inequality by utilizing the Cauchy-Schwarz inequality twice,i.e.,

$$(\sum x_i)(\sum\frac{x_i^3}{x_{i+1}^2})\geq (\sum\frac{x_i^2}{x_{i+1}})^2$$


$$(\sum x_i)(\sum\frac{x_i^2}{x_{i+1}})\geq (\sum x_i)^2$$

  • $\begingroup$ Can you explain second inequality, please? $\endgroup$ – fdhd Nov 11 '12 at 14:10
  • 1
    $\begingroup$ @user46034:It is just $$(\sum x_{i+1})(\sum\frac{x_i^2}{x_{i+1}})\geq (\sum x_i)^2$$ then it is easy to use Cauchy-Schwartz inequality to get the result above. $\endgroup$ – zy_ Nov 11 '12 at 14:14
  • $\begingroup$ Why do you change $x_{i}$ with $x_{i+1}$? Are they equal? Or Cauchy-...? I really do not understand $\endgroup$ – fdhd Nov 11 '12 at 14:17
  • 1
    $\begingroup$ $x_i$ and $x_{i+1}$ are not equal,but their sums are equal,say,$x_1+x_2+\cdots+x_n=x_2+x_3+\cdots+x_{n+1}$. $\endgroup$ – zy_ Nov 11 '12 at 14:19

$$3^n\frac{x_1^3}{x_2^2} + 2\cdot 3^{n-1}\frac{x_2^3}{x_3^2} +4\cdot 3^{n-2}\frac{x_3^3}{x_4^2}+\cdots+2^{n-1}\cdot3\frac{x_{n-1}^3}{x_n^2}+2^n\frac{x_n^3}{x_1^2}\ge (3^n-2^n)x_1$$

By Weighted AM-GM. (Note that the sum of the coefficients is the expression for $\frac{3^n-2^n}{3-2} = 3^n-2^n$)

Adding cyclicly and dividing by $3^n-2^n$, we find

$$\sum_{i=1}^n\frac{x_i^3}{x_{i-1}^2} \ge \sum_{i=1}^n x_i$$

Now note that another application of AM-GM gives $\frac{x_i^3}{x_{i-1}^2}+x_i \ge 2\frac{x_i^2}{x_{i-1}}$, so summing over all $i$,

$$\sum_{i=1}^n\frac{x_i^3}{x_{i-1}^2} + \sum_{i=1}^n x_i \ge \sum_{i=1}^n\frac{x_i^2}{x_{i-1}}$$

So then, $$2\sum_{i=1}^n\frac{x_i^3}{x_{i-1}^2} \ge \sum_{i=1}^n\frac{x_i^3}{x_{i-1}^2} + \sum_{i=1}^n x_i \ge \sum_{i=1}^n\frac{x_i^2}{x_{i-1}}$$

  • $\begingroup$ but this is different from the original inequality $\endgroup$ – Christmas Bunny Nov 22 '13 at 0:51

Multiply both sides by $$\prod_{i=1}^{n} x_i^2$$ then just use Muirhead inequality.

  • $\begingroup$ I don't think this works; Muirhead's inequality requires symmetric sums, not just cyclic sums. $\endgroup$ – only Nov 11 '12 at 13:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.